The Little Red Hen makes a pizza - Sturges, Philemon; Walrod, Amy (New York : Scholastic Inc., 2001)
In this version of the traditional tale, the duck, the dog, and the cat refuse to help the Little Red Hen make a pizza but do get to participate when the time comes to eat it.
Originally published by Dutton Children's Books.
Keywords: Folklore; Poules; Folklore; Pizza; Litterature de jeunesse anglaise; Folklore